APPLICATION OF STORYTELLING TECHNIQUES IN IMPROVING SPEAKING SKILLS IN ELEMENTARY SCHOOL STUDENTS - M. Nur Hakim (IJLECR (International Journal of Language Education and Cultural Review), 2018)
Learning to speak is one of the obstacles experienced by students of class III MIS Darul Ulum Muhammadiyah Bulukumba. These obstacles appear from a lack of vocabulary, fluency, and understanding. Therefore, this study aims to improve students' speaking skills through the application of storytelling techniques. The research conducted is action research which includes the stages of planning, action, observation, and reflection. Data collection is done through observation, interviews, and speaking tests, while the data analysis is done descriptively qualitatively and quantitatively. The results of this study indicate that during the application of storytelling techniques there is an increase in speaking skills that appear from the assessment indicators, which include: pressure, grammar, vocabulary, fluency, and understanding. The results of the acquisition in the first cycle of 65.33 and an increase in cycle 2 of 73.78. Increased learning outcomes from cycle 1 to cycle 2 indicate that storytelling can have a positive impact on learning to speak.